Semantic Ambiguity in Translation: A Comparative Study Between English and Indonesian - Tias Bastian Saragih; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study investigates semantic ambiguity in translation, with a specific focus on lexical ambiguity in the English–Indonesian translation of the Cinderella short story. Grounded in Nida and Taber’s theory of semantic equivalence and Baker’s framework of non-equivalence, the research examines how lexical items in the source language may lead to multiple interpretations or shifts in meaning when translated into the target language. Using a qualitative content analysis method, the study identifies patterns of meaning distortion resulting from ambiguous or culturally loaded words. The findings indicate that lexical ambiguity significantly contributes to semantic non-equivalence, often causing partial or lost meaning that undermines narrative clarity and coherence. The study highlights the critical role of contextual awareness and lexical precision in literary translation to preserve intended meaning.